A heterometallic ferrimagnet based on a new TTF-bis(oxamato) ligand. Issue 12 (7th March 2017) - Cui, Long; Ge, Jing-yuan; Leong, Chanel F.; D'Alessandro, Deanna M.; Zuo, Jing-Lin
Abstract : An interesting heterometallic one-dimensional complex {[Cu(TTF-opba)][Mn(CH3 OH)2 ]} n based on a π-extended TTF ligand was prepared through the method of "metalloligand". It retains the redox activity and shows ferrimagnetic behavior. Abstract : An oxamato unit has been introduced into a tetrathiafulvalene (TTF) system for the first time via direct condensation, generating a new π-extended TTF ligand, TTF-Et2 H2 opba (opba = ortho -phenylenebis-oxamato). On the basis of this ligand, the Cu(ii ) complex [( n -Bu)4 N]2 [Cu(TTF-opba)] (1 ) has been obtained. By employing this complex as a "metalloligand", we have successfully prepared an interesting heterometallic one-dimensional complex {[Cu(TTF-opba)][Mn(CH3 OH)2 ]} n (2 ), via coordination of the free carbonyl-oxygen atoms of the two oxamato groups with Mn(ii ) ions. The new compounds have been structurally characterized, and their electrochemical and magnetic properties probed. Complex2 shows a ferrimagnetic behavior with g = 1.96 and J = −22.36 cm −1 .